The Effect of a Risk-Based Audit Approach on Tax Compliance Intention: The Moderating Role of Procedural Justice - Johannes Pinta Surbakti; Renny Maisyarah; M. Irsan Nasution (CV. Doki Course and Training, 2026)
Tax compliance remains a strategic challenge in self-assessment tax systems, particularly among individual taxpayers and micro, small, and medium enterprises (MSMEs), where compliance levels tend to fluctuate. In response to this challenge, the Indonesian tax authority has increasingly adopted a Risk-Based Audit (RBA) approach, which prioritizes audit activities based on taxpayers' risk profiles to improve enforcement efficiency and effectiveness. However, the impact of RBA on taxpayers' compliance intention is not solely determined by enforcement mechanisms, but also by taxpayers' perceptions of procedural justice applied by tax authorities. This study aims to examine the effect of Risk-Based Audit on tax compliance intention and to analyze the moderating role of procedural justice in this relationship. The research employs a quantitative approach using survey data collected from individual taxpayers and MSMEs registered in Medan City. Data were obtained through structured questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS software. The analysis includes evaluation of the measurement model through validity and reliability testing, as well as structural model assessment to test the proposed hypotheses. The findings are expected to demonstrate that Risk-Based Audit has a positive effect on tax compliance intention, and that procedural justice strengthens this relationship. This study contributes theoretically by integrating deterrence theory, procedural justice, and behavioral intention perspectives within a single moderation model in the tax compliance literature. Practically, the results provide policy-relevant insights for tax authorities in designing risk-based audit strategies that are not only effective in enforcement, but also perceived as fair and legitimate, thereby fostering sustainable voluntary tax compliance.